Glutamate Carboxypeptidase II in Aging Rat Prefrontal Cortex Impairs Working Memory Performance - Datta, Dibyadeep; Leslie, Shannon N.; Woo, Elizabeth; Amancharla, Nishita; Elmansy, Ayah; Lepe, Miguel; Mecca, Adam P.; Slusher, Barbara S.; Nairn, Angus C.; Arnsten, Amy F. T. (Frontiers in Aging Neuroscience, 2021)
GCPII (glutamate carboxypeptidase II) expression in brain is increased by inflammation, and reduces NAAG (N-acetyl aspartyl glutamate) stimulation of mGluR3 signaling. Genetic insults in this signaling cascade are increasingly linked to cognitive disorders in humans, where increased GCPII and or decreased NAAG-mGluR3 are associated with impaired prefrontal cortical (PFC) activation and cognitive impairment. As aging is associated with increased inflammation and PFC cognitive deficits, the current study examined GCPII and mGluR3 expression in the aging rat medial PFC, and tested whether GCPII inhibition with 2-MPPA (2-(3-mercaptopropyl) pentanedioic acid) would improve working memory performance. We found that GCPII protein was expressed on astrocytes and some microglia as expected from previous studies, but was also prominently expressed on neurons, and showed increased levels with advancing age. Systemic administration of the GCPII inhibitor, 2-MPPA, improved working memory performance in young and aged rats, and also improved performance after local infusion into the medial PFC. As GCPII inhibitors are well-tolerated, they may provide an important new direction for treatment of cognitive disorders associated with aging and/or inflammation.